The Effect of Arm Muscle Power, Waist Flexibility, And Self-Confidence on Front Handspring Skills in Artistics Gymnastics - Lubis, Hafiz Yazid; Setiakarnawijaya, Yasep; Jauhari, Mansur (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
This study aims to determine the effect of arm muscle power, waist flexibility and self-confidence on front handspring skills of students of Medan State University Sports Coaching Education. Data collection was carried out in November 2021 at the Faculty of State University of Medan. The research method used in this study is a survey method with path analysis techniques. The sample used in this study amounted to 84 students who came from first semester students of Sports Coaching Education. The first test was taken, namely the measurement of arm muscle power and waist flexibility measurement, then continued with measuring self-confidence and front handspring skills. The hypothesis testing technique used in this study is using path analysis techniques. The data obtained will go through a data analysis process through SPSS. The results of this study indicate that there is a direct effect of the variable X1 on X3 = 0.171, the direct effect of the variable X2 on X3 = 0.677, the direct effect of the variable X1 on Y = 0.157, the direct effect of the variable X2 on Y = 0.199, the direct effect of the variable X2 on Y = 0.199, the direct variable X3 on Y = 0.651, indirect effect of variable X1 on Y through X3 = 0.111 and indirect effect of variable X2 on Y through X3 = 0.440.